MORPHOLOGICAL CHANGES IN THE PREFRONTAL CORTEX IN METABOLIC SYNDROME AND SLEEP DEPRECATION - Shamsiddinov, Sherzod (International Conference on Health & Technology, 2026)
Morphological changes in the prefrontal cortex in metabolic syndrome and sleep deprivation include reduced dendritic spines, decreased gray matter volume, decreased neuroplasticity, and chronic neuroinflammation. These impairments, compounded by each other, lead to significant cognitive deficits (particularly working memory and self-control) and emotional dysregulation.